Maraknya Tingkat Pernikahan Dini pada Masa Covid-19: (Studi Kasus di Pengadilan Agama Kabupaten Pohuwato) - Rion Monoarfa; Udin Hamim; Nopiana Mozin (MIMBAR ADMINISTRASI FISIP UNTAG Semarang, 2024)
. This research aims to discuss the risks of early marriage during Covid-19 (case study at the Pohuwato Regency Religious Court). This research uses a qualitative approach with a descriptive approach where data is obtained through observation, interviews and documentation so that the data obtained is in accordance with conditions occurring in the field. The findings in this research are that the efforts of the Pohuwato Regency religious court in preventing the rise of early marriage have been quite good. This is shown by the number of early marriages in 2021 amounting to 152 people, in 2022 only 87 people and in 2023 72 people, thus the number of early marriages in Pohuwato Regency in the last two years has decreased. Meanwhile, the factors that prevent religious courts from preventing early marriage are caused by promiscuity and the government.